Asian financial integration during the pre-and post crisis periods. - Mohamed, Azali; Lee, Chin (Serials Publications, 2009)
As the economies of Asian have moved towards closer economic ties and trade integration in recent years, the establishment of regional exchange rate arrangement is becoming an important regional policy concern, particularly in the wake of the Asian currency crisis of 1997. Financial integration in ASEAN+3 is assessed in this paper by examining the time-series stochastic behaviour and cointegration in a set of eight ASEAN+3 currencies in pre-crisis, crisis and post-crisis periods. Significant non-stationarity, and the presence of unit roots were documented for each currency in each sample period. The results of cointegration analysis showed that the currencies are not cointegrated during the pre-crisis period. Evidence of cointegration was found among a few Asian currencies in the crisis and post-crisis periods. These findings have important implications for understanding the potential of developing a common currency area.